Quality Enhancement: Vocational Skill Development And Entrepreneurship (International Journal of Scientific Research and Management (IJSRM), 2018)
India is fastest growing country in the world. We have largest technical manpower. In India the emphasis has been on general education , with vocational skill education and entrepreneurship at the receiving end. Coz of which large number of people are still unemployed. The article shows the recent growth in the area of vocational skills and entrepreneurship. India has only 4% skilled workforce. In the year 2022 109.73 million skilled manpower are required. The way in which innovation higher and vocational skill develop competencies for entrepreneurship is analyzed. Various ministers are trying to impart vocational courses through innovative institutions, specially launched for the purpose. In doing so the government is trying to maintain the quality of these courses. Under the 11th plan, vocationalization of education has received a boost with more funds being allotted for the purpose. The article ends with the recommendations on promoting vocational skill and entrepreneurship in society and the reforms that should be done in this field